2012
DOI: 10.5830/cvja-2012-003
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiogenic, anti-angiogenic and vasoactive factors in pre-eclamptic African women : early- versus late-onset pre-eclampsia

Abstract: The pathogenesis and aetiology of pre-eclampsia (PE) is still unclear. We investigated the role of angiogenic, anti-angiogenic and vasoactive factors in black South African women with early- and late-onset PE. Serum soluble fms-like tyrosine kinase 1 (sFlt-1), soluble vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) levels were determined using the ELISA technique, and placental mRNA expression levels of sFlt-1, VEGF, PlGF and AT1 receptors were determined using real-time PCR.Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
2
19
0
1
Order By: Relevance
“…This finding suggests that sFlt-1 may be a good marker for earlyonset PE. Previous studies have supported the hypothesis that an earlier onset of PE corresponds with higher sFlt-1 levels [26,27]. However, there are still some discrepancies in the reported sFlt-1 protein levels between studies.…”
Section: Discussionmentioning
confidence: 91%
“…This finding suggests that sFlt-1 may be a good marker for earlyonset PE. Previous studies have supported the hypothesis that an earlier onset of PE corresponds with higher sFlt-1 levels [26,27]. However, there are still some discrepancies in the reported sFlt-1 protein levels between studies.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings support the hypothesis of common pathogenic factors in preeclampsia and CHD, particularly between early‐onset preeclampsia and severe CHD. The pathophysiologic pathway in early‐onset preeclampsia is probably different from preeclampsia close to term, which may explain that the association with severe CHD differed by subtypes of preeclampsia.…”
Section: Commentmentioning
confidence: 99%
“…Most previous studies on angiogenic and antiangiogenic factors were conducted in White participants and there is a paucity of information on other ethnic groups. 31,32 Black women were found to have slightly higher levels of PlGF, sEng, and sVEGFR-1 than White women and women of other races in one study 33 but in another study no difference in PlGF and sVEGFR-1 was found compared to White women. 34 A study of sVEGFR-1 levels by parity 35 also did not find significant differences in PlGF and sVEGFR-1 levels within the first or second pregnancies of Hispanic women compared to White women.…”
Section: Commentmentioning
confidence: 89%
“…3 In the last decade a two-stage pathogenic model has gained acceptance as the underlying pathophysiology of early-onset preeclampsia. 31,37-40 In the first stage, inadequate placentation due to shallow cytotrophoblastic invasion restricts blood supply to the placenta and creates a hypoxic placental environment in the first trimester. Oxidative stress then induces ischemic lesions to the placenta, which may promote the release of a variety of molecules including but not limited to PlGF, sEng, and sVEGFR-1 into maternal circulation.…”
Section: Commentmentioning
confidence: 99%